2014
DOI: 10.1136/bmjopen-2014-005710
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between socioeconomic status and type 2 diabetes: results from Korea National Health and Nutrition Examination Survey (KNHANES) 2010–2012

Abstract: ObjectiveTo examine the relationship between socioeconomic status (SES) and type 2 diabetes using the Korea National Health and Nutrition Examination Survey (KNHANES) 2010–2012.DesignA pooled sample cross-sectional study.SettingA nationally representative population survey data.ParticipantsA total of 14 330 individuals who participated in the KNHANES 2010–2012 were included in our analysis.Primary outcomePrevalence of type 2 diabetes.ResultsThe relationship between SES and type 2 diabetes was assessed using lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
84
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 38 publications
11
84
1
Order By: Relevance
“…Figure 1 shows the map of the WPR, and Table 2 reports the temporal changes in the prevalence of diabetes in these countries. The rising trend in the developing countries is considerably steeper compared with the developed countries (1,12,14,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In recent decades, apart from the WHO STEPS studies (11), there have been very few national diabetes studies for the Pacific Ocean nations (14).…”
Section: The Diabetes Epidemic In the Pacific Region And In Asia Wprmentioning
confidence: 99%
“…Figure 1 shows the map of the WPR, and Table 2 reports the temporal changes in the prevalence of diabetes in these countries. The rising trend in the developing countries is considerably steeper compared with the developed countries (1,12,14,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In recent decades, apart from the WHO STEPS studies (11), there have been very few national diabetes studies for the Pacific Ocean nations (14).…”
Section: The Diabetes Epidemic In the Pacific Region And In Asia Wprmentioning
confidence: 99%
“…In recent preceding studies on the association between diabetes mellitus and social factors in the general population, those with lower education level had a higher proportion of diabetes mellitus [14,15], as did single women [14] and divorced and widowed women [16]. Our study assessing the association diabetes mellitus has with socio-environmental factors among patients with schizophrenia provides new clues for preventing diabetes mellitus complications among these patients.…”
Section: Discussionmentioning
confidence: 71%
“…As for factors assessing the relationships between schizophrenia and diabetes mellitus [6,[14][15][16][17][18][19], we gathered the following items: age, gender, total length of hospitalization during the study period, and prescription of antidiabetics from health insurance claims, and body mass index (BMI), psychological symptoms, activities of daily living disorder (ADL disorder), current/past history of hypertension, current/past history of hyperlipidemia, prescription of antipsychotics, and socio-environmental factors such as education history, type of hospitalization, type of social insurance, marital status, and living arrangement from electronic medical records. Among patients with schizophrenia hospitalized since before December 31, 2012, we counted the total length of hospitalization from January 1, 2013, and defined 730 days as maximal length.…”
Section: Data Collectionmentioning
confidence: 99%
“…It is observed from the present study results that occurrence of diabetes is more common among females (59.00 per cent) than males (41.00 per cent) and these findings are in tuned with the findings of Ahmed et al, (2011) who also reported greater prevalence of diabetes among females (8.3 per cent) than males (3.6 per cent). However, Hwang and Shon (2014) found that there is greater prevalence of diabetes (55.5 per cent) among males than the females (45.5 per cent).…”
Section: Materials and Methods:-mentioning
confidence: 82%